The association between arterial-end-tidal carbon dioxide difference and outcomes after out-of-hospital cardiac arrest. (December 2022) - Abrahamowicz, Aleksandra A.; Counts, Catherine R.; Danielson, Kyle R.; Bulger, Natalie E.; Maynard, Charles; Carlbom, David J.; Swenson, Erik R.; Latimer, Andrew J.; Yang, Betty; Sayre, Michael R.; Johnson, Nicholas J.
Abstract: Aim: We sought to determine if the difference between Pa CO2 and ET CO2 is associated with hospital mortality and neurologic outcome following out-of-hospital cardiac arrest (OHCA). Methods: This was a retrospective cohort study of adult patients who achieved return of spontaneous circulation (ROSC) after OHCA over 3 years. The primary exposure was the Pa CO2 -ET CO2 difference on hospital arrival. The primary outcome was survival to hospital discharge. The secondary outcome was favorable neurologic status at discharge. We used receiver operating characteristic (ROC) curves to determine discrimination threshold and multivariate logistic regression to examine the association between the Pa CO2 -ET CO2 difference and outcome. Results: Of 698 OHCA patients transported to the hospitals, 381 had sustained ROSC and qualifying ET CO2 and Pa CO2 values. Of these, 160 (42%) survived to hospital discharge. Mean ET CO2 was 39 mmHg among survivors and 43 mmHg among non-survivors. Mean Pa CO2 -ET CO2 was 6.8 mmHg and 9.0 mmHg ( p < 0.05) for survivors and non-survivors. After adjustment for Utstein characteristics, a higher Pa CO2 -ET CO2 difference on hospital arrival was not associated with hospital mortality (OR 0.99, 95% CI: 0.97–1.0) or neurological outcome. Area under the ROC curve or Pa CO2 -ET CO2 difference was 0.56 (95% CI 0.51–0.62) compared with 0.58 (95% CI 0.52–0.64) for ET CO2 . Conclusion: Neither Pa CO2 -ET CO2 nor ET CO2 were strong predictors of survival or neurologic status at hospital discharge. While they may be useful to guide ventilation and resuscitation, these measures should not be used for prognostication after OHCA.